Subjective grounds for expanding the powers of the President of the Russian Federation - Nitsevich Viсtor (Eastern Review, 2020)
The article is devoted to a little-studied side of authority, in particular the authorities of the President of Russia. Exploring the constitutional scope of power, we can say that the President of Russia has a sufficiently large amount of power, backed up by the legal provisions of the Constitution. However, in practice, it has turned out that not only their influence but the power of the President has a wider scope. First of all, the article notes the subjective grounds and mechanisms of power over the chairman of the government and the terms of his appointment. In this case, the key role is played by the political party United Russia, which was created by the President, although the President is outside the party system of Russia. A substantial expansion of the power of the President occurred as a result of the creation of federal districts and the formation of an institution of plenipotentiaries. The rationale is given that the change of legal norms for the election of governors, where the President plays the main role in nominating candidacy, and the procedure for registering them is entirely determined by the United Russia political party under his control, ultimately expanded the scope of authority of the President. In disclosing the subjective grounds for expanding the power of the President of the Russian Federation, so-called “approvals” of candidacy for various senior positions of state and municipal service, as well as of the security and control bodies play a part. The rating of the President was a massive subjective basis that allowed him to expand the scope of his power. The study of public confidence in the President allowed one to see the dependence of the expansion of his power on the level of his support by citizens of the Russian Federation.